2013
DOI: 10.1111/nhs.12060
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension prevalence, awareness, and control in Arab countries: A systematic review

Abstract: One billion of the world’s population has hypertension, resulting in four million deaths per year. Data on the prevalence of hypertension in the Arab world are very limited. This review summarizes existing knowledge regarding prevalence, awareness, and control of hypertension in Arab countries. The PubMed, Cochrane Library, Scopus, and CINAHL databases were searched for publications on HTN among Arab people from 1980 to January 2011. Only 13 studies were identified in the literature from 10 Arab countries. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 18 publications
8
103
2
1
Order By: Relevance
“…The findings demonstrated that those had higher education levels (such as doctorate and master holders) had less vulnerability to develop HTN. Similar finding was reported by the previous literature (14,16) which found that education significantly reduces the prevalence of HTN illness. A possible explanation of these findings is that higher level of education is frequently related with better awareness concerning healthy lifestyle and HTN associated risk factors.…”
Section: Risk Factors Of Htnsupporting
confidence: 92%
“…The findings demonstrated that those had higher education levels (such as doctorate and master holders) had less vulnerability to develop HTN. Similar finding was reported by the previous literature (14,16) which found that education significantly reduces the prevalence of HTN illness. A possible explanation of these findings is that higher level of education is frequently related with better awareness concerning healthy lifestyle and HTN associated risk factors.…”
Section: Risk Factors Of Htnsupporting
confidence: 92%
“…[2][3][4][5][6][7] However, data regarding the prevalence of hypertension in South Asians are controversial, unlike the results concerning to the high prevalence of coronary heart disease (CHD) in this population. 8 It has been demonstrated that slowing breathing to 6 breaths per minute can reduce blood pressure (BP) in hypertensive patients, patients with chronic heart failure, and patients with chronic obstructive pulmonary disease, but not in normotensive control subjects.…”
Section: -7mentioning
confidence: 99%
“…Little is known about predisposition of hypertension among Arabs; however, a few studies reported that hypertension is prevalent in Arabic population. 6,7 Previously, it was shown, that Arabs had enhanced pressor response to orthostasis, despite similar baseline BP among Caucasians, Africans and Indians. 16 Possibly, the low cardiovagal activity found in the current study in normotensive Arabs may be relevant to their predisposition to hypertension.…”
Section: Ethnic/racial Differences In Hemodynamic and Hrv Indicesmentioning
confidence: 99%
“…5 Hypertension will play a major role in the ongoing cardiovascular disease epidemic, and early recognition and treatment of hypertension are essential to the prevention of cardiovascular disease and its sequelae. 6,7 Although a number of studies have reported the prevalence of hypertension in low-and middle-income countries, 2,8,9 few have explicitly studied hypertension within urban informal settlements or slums, which are communities with limited access to the formal healthcare system. [10][11][12][13][14][15][16][17][18][19] In 2003, the United Nations Human Settlements Program (UN-Habitat) operationally defined slums as urban areas characterized by their poor sanitation infrastructure, limited access to safe water, poor structural housing quality, and overcrowding.…”
Section: Introductionmentioning
confidence: 99%